Design and Simulation of Bethe Hole Coupler Using Ridge Gap Waveguide Technology for Satellite Communication - Kamran Salehian; Gholamreza Moradi (AUT Journal of Electrical Engineering, 2024)
In this research paper, an innovative approach is employed to design and simulate a Bethe hole coupler utilizing ridge gap waveguide (RGW) technology. The RGW structure includes two parallel metal plates, a ridge, and strategically placed pins. To achieve the coupler structure, we place two waveguides facing each other, and between these two waveguides, there is a perforated metal plate. Initially, four holes are set in the plate between the waveguides to enhance the coupling coefficient's bandwidth. The radius of the holes is initially calculated and designed to achieve a 20 dB coupling. The validity of the design is confirmed using CST software. RGW transition design is usually more difficult than other gap waveguide structures. For this reason, in this paper, a technique called Step Ridge Waveguide Excitation (SRWE) is introduced for efficient excitation of the designed coupler. The proposed methodology is implemented in the Ku band, which is suitable for satellite communication with high bandwidth. The dimensions of our structure are 50mm × 30mm × 17mm. Additionally, a 20±2 dB coupling coefficient is obtained for a fractional bandwidth (FBW) of approximately 29%. It demonstrates a directivity range of 6-16 dB, and the isolation is lower than 23 dB, surpassing the performance of similar previous works.